Revolutionary superposition layout method for topology optimization of nonconcurrent multiload models: Connecting‐rod case study. (26th November 2020) - Alkalla, Mohamed G.; Helal, Mahmoud; Fouly, Ahmed
Abstract: This article proposes a new approach called revolutionary superposition layout (RSL) for obtaining optimum designs of nonconcurrent multiloads structures in general, and for connecting rod (CR) in particular. Since the compression and tension resulted from the combustion and exhaust strokes are nonconcurrent loads, the importance of this approach arises up. RSL depends on combining the optimum‐design layouts obtained from different individual nonconcurrent load cases into one resultant design. This final design efficiently sustains all different loads applied to it. RSL presents a simple, less computational effort in the dynamic environment, and less time‐consuming method. RSL has been compared with a multiload optimization method called bound formulation (BF) for obtaining the optimum design of some simple models before dealing with the CR model afterward. Two distinctive optimum topological designs of CR produced by RSL have proved their feasibility and achieved considerable improvements against both the conventional CR design being used nowadays in the automotive industry and the BF method designs, as well. A comparative study between them was accomplished based on both structural and modal analyses in ANSYS. As a result, the proposed RSL design shows a significant reduction of compliance, displacement/deflection and mass moment of inertia by 57.2%, 68.7%, and 5.9%, respectively, compared with conventional one.